Desenvolvimento de queijo petit-suisse adicionado de cultura com potencial probiótico a partir do leite desnatado de búfalas - OLIVEIRA, Josué de Souza (2018)
The use of milk from buffaloes and microorganisms obtained from the fermentation of cocoa for the production of probiotic foods is still little known. The present work aimed to develop a petit-suisse type cheese using skimmed buffalo milk and lactobacillus isolated from the cocoa fermentation. To evaluate the effects of the use of sweeteners on the quality of petit-suisse cheese, four formulations with different concentrations of sweeteners were elaborated, being evaluated the physical-chemical characteristics, the centesimal composition, the microbiological and sensorial quality. The effects of incubation, the use of sweeteners and lactobacilli on the quality of petit-suisse produced by enzymatic coagulation were evaluated from the preparation of six treatments, varying the incubation time (0 and 12 hours), the concentration of sweeteners (0 and 50%) and the addition of lactobacilli (without lactobacilli, with Lactobacillus fermentum TcUESC01, with Lactobacillus plantarum TcUESC02 and simultaneously with these two lactobacilli), through the evaluation of physico-chemical characteristics, viability of lactobacilli and sensorial aspects during storage. The evaluation of the effects of the use of lactobacilli on the quality of petit suisse cheese was obtained from the preparation of four formulations: without addition of lactobacilli (control), added with L. fermentum TcUESC01 (Lferm), L. plantarum TcUESC02 (Lplan) and simultaneously, these two lactobacilli (Lplan + Lferm), evaluating the physico-chemical characteristics, lactobacilli viability, chemical composition, instrumental texture profile, microbiological and sensorial quality. The probiotic potential of lactobacilli was evaluated using in vitro (antagonistic) and in vivo (mortality, translocation, morphometry, histopathology, IgA determination and cytokine expression) assays performed in mice challenged with Salmonella Typhimurium. The formulations with 50%, 75% and 100% of sweeteners were classified as "light" and with 100% sweeteners, as "diet". In the sensory evaluation, the treatments with 25% and 50% were the most accepted in the flavor and overall impression attributes, also more preferred, with the intention of buying 76% of the tasters. The cheese produced with addition of the two lactobacilli simultaneously, without the addition of sweeteners and without incubation presented the best result in the sensorial evaluation during the period of 42 days of storage. Samples of cheese with lactobacilli showed viability greater than 7.00 log CFU / g during storage. All formulations were designated as "Free of total fats" and met the limits recommended in Brazilian legislation on chemical composition, probiotic viability and microbiological evaluation. The Lplan and Lferm formulations stand out as promising for the development of a probiotic petit-suisse type cheese with fat-free buffalo milk. L. fermentum TcUESC01 and L. plantarum TcUESC02 were potential probiotics based on better results obtained by in vitro evaluations (higher production of compounds with antimicrobial activity), as well as in vivo experiments (greater survival after challenge of enteropathogen and production of IgA in the ileum, lower hepatic and splenic enteropathogen translocation, lower histopathological lesions in the liver and better anti-inflammatory pattern demonstrated by cytokine expression).